Does being assisted by care workers affect antipsychotics prescription among older people discharged from hospital?. Issue 10 (10th November 2016) - Di Rosa, Mirko; Fabbietti, Paolo; Corsonello, Andrea; Fusco, Sergio; Sganga, Federica; Volpato, Stefano; Ruggiero, Carmelinda; Onder, Graziano; Lattanzio, Fabrizia
Abstract : Aim: Several factors can affect antipsychotic prescriptions, among which, caregivers. However, whether being assisted by a care worker might increase the rate of antipsychotic prescriptions at discharge from acute care hospital has not been previously investigated. We aimed to investigate whether being assisted by a care worker is associated with increased use of antipsychotics among older patients discharged from acute care hospitals. Methods: The present series consisted of 928 patients not taking antipsychotics at admission in seven acute care wards of geriatric medicine in Italy (mean age 80.8 ± 7.2 years, 54.9% women). The outcome of the study was defined as receiving an antipsychotic prescription at discharge. Patients were grouped according to their living conditions as follows: (i) living alone; (ii) living only with care worker; (iii) living with care worker and family members; and (iv) living only with family members. The association between study variables and antipsychotic prescription at discharge was investigated by logistic regression analysis. Results: After adjusting for potential confounders, being assisted by care workers was significantly associated with the outcome (OR 2.64, 95% CI 1.21–5.75). Diagnosis of dementia (OR 2.73, 95% CI 1.65–4.51), instrumental activities of daily living limitations (OR 1.12, 95% CI 1.05–1.21) and delirium during stay (OR 3.87, 95% CI 2.01–7.47) also qualified as independent correlates of antipsychotic prescription at discharge. Conclusions: Being assisted by care workers could increase the likelihood of receiving antipsychotics at discharge from acute care hospitals.Geriatr Gerontol Int 2017; 17: 1707–1713.